(3MhGpT Ydi GdCdajIs - (3YHO Gddg Hf jhSa Hf CMeO GdCfUGQj GdeUQj GdfMhj , LeGd GdOjf , CHh eMeO, GHf gTGe J (B761 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3cdGefG daX eajO Edi BNQg bhdg(B: (3eajO UaI dG NHQ HYO NHQ, dCf GdChd dG jSJbd HGdNHQjI s
(3BNQgG (B:s
(3Ke MQcJ GdChdi HGdaJM aGfbdHJ GdChdi hGdKGfjI CdakG Ke hGhkG, hef bGd HGdcSQ bGd Wj, hef Ve Ve s
(3fSNI ocJHJ Hbde eYJGO eged GdfbW CMjGfkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B110 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B154s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3fMh (B187) s
Keywords: (3GdfMhs